2009
DOI: 10.1021/op9002054
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a New Manufacturing Route to the Novel Anticonvulsant, SB-406725A

Abstract: The development of an efficient manufacturing route to 3-acetyl-N-(5,8-dichloro-1,2,3,4-tetrahydro-7-isoquinolinyl)-4-(1-methylethoxy)-benzamide hydrochloride SB-406725A (1) is described. The synthesis begins with dichlorination of isoquinoline, followed by nitration using nitronium tetrafluoroborate in sulpholane. Nitroisoquinoline (12) was hydrogenated under pressure using Pt/ C. The resultant tetrahydroisoquinoline (13) was selectively coupled with benzoate side chain (15) under base-promoted conditions usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Sulfolane is a highly stable and attractive alternative to common dipolar aprotic solvents such as DMSO, DMF, DMAc, and NMP. , Because of its high stability toward strong acids and oxidizing agents, as well as its thermal stability, sulfolane is a solvent that can be utilized under a wide range of reaction conditions. Sulfolane has been used as a solvent for aromatic nitration reactions using nitronium tetrafluoroborate ([NO 2 ]­BF 4 ) as a nitrating reagent . However, to the best of our knowledge, there are no reports of the use of sulfolane in combination with concentrated or fuming HNO 3 .…”
Section: Resultssupporting
confidence: 71%
“…Sulfolane is a highly stable and attractive alternative to common dipolar aprotic solvents such as DMSO, DMF, DMAc, and NMP. , Because of its high stability toward strong acids and oxidizing agents, as well as its thermal stability, sulfolane is a solvent that can be utilized under a wide range of reaction conditions. Sulfolane has been used as a solvent for aromatic nitration reactions using nitronium tetrafluoroborate ([NO 2 ]­BF 4 ) as a nitrating reagent . However, to the best of our knowledge, there are no reports of the use of sulfolane in combination with concentrated or fuming HNO 3 .…”
Section: Resultssupporting
confidence: 71%
“…The nitration of 5,8-dichloroisoquinoline (45) is very difficult under standard conditions; either there is no conversion, or the reaction delivers a very low yield of the wanted product, in some cases with extremely long reaction times. 22 Walker et al found that nitronium salts as a neutral source of the nitronium ion gave an improved conversion of the 5,8-dichloroisoquinoline. The authors found sulfolane to be the solvent of choice; although dichloromethane could be used as a cosolvent, other solvents were either incompatible or led to no reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The treatment of carbon-14-labeled standard 18 with BBr 3 provided intermediate acid 19 (Scheme ). Without further purification, 19 was treated with NO 2 BF 4 /sulfolane in CH 3 CN to afford the desired radiotracer 20 in 59% yield . Pleasingly, ecotoxicology studies conducted using standards 9 and 20 showed low toxicity to nontarget species.…”
Section: Results and Discussionmentioning
confidence: 99%